“TRANSFORMAÇÕES POLÍTICAS” E PERSISTÊNCIA DAS DESIGUALDADES DE ACESSO À ESCOLA - Antonio Paulino de Sousa (Universidade Federal do Maranhão, 2018)
This article uses empirical data provided by public and private school students, analyzed in the light of the theorists Labov, Bourdieu and Bernstein. From the analysis of the subjects preferred by the students and their oral and written discourses, it was shown that the linguistic stratification is correlated with the social and scholastic inequalities, being that the students of the favored classes take advantage of the students of the disadvantaged classes in the access to the school, which has a linguistic code distant from these students and close to those. It concludes that, the school operates a process of naturalization of social inequalities, in this school model, a process of sociocultural transformation is not envisaged.